New and little known digger wasps of the genus Ammophila W. Kirby, 1798 (Hymenoptera: Apoidea: Sphecidae) from Central Asia - Danilov, Yuriy N. (Zootaxa, 2015)
Five species of Ammophila are treated. The lectotype of Ammophila separanda F. Morawitz, 1891 is designated and illustrated. The holotype of Ammophila cellularis Gussakovskij, 1930 is redescribed and illustrated. Two new species, Ammophila barkalovi sp. nov. (Kazakhstan) and A. pevtsovi sp. nov. (China), are described and illustrated. The hitherto unknown female of A. vetuberosa Li & Yang, 1994 is described.